Generation and reception of the up to 28Gbit/s optical signals with the limited-bandwidth components - Czyzak, Pawel; Mazurek, Pawel; Turkiewicz, Jaroslaw Piotr (Photonics Letters of Poland, 2012)
The utilization of limited-bandwidth electro-optical components in generation and reception of the high-speed optical signals up to 28 Gbit/sis investigated. The influence of the modulator and photodiode electrical bandwidth on the signal quality as well as the influence of chromatic dispersion on the transmitted signal is studied. The results show, that the signals can be generated and properly received without significant loss of the chromatic dispersion tolerance in components with a limited-bandwidth. Generation of up to 28 Gbit/s signals with a 12.5 GHz modulator is demonstrated and evaluated. Full Text: PDF References P. K. L. Yu, G. L. Li, "Optical Intensity Modulators for Digital and Analog Applications," JOURNAL OF LIGHTWAVE TECHNOLOGY, VOL. 21, NO. 9, 2003. CrossRef Ed L. Wooten et. al., "A Review of Lithium Niobate Modulators for Fiber-Optic Communications Systems," IEEE JOURNAL OF SELECTED TOPICS IN QUANTUM ELECTRONICS, vol. VOL. 6, no. NO. 1, 2000. CrossRef Thorlabs Inc. (2012, Sep.) Thorlabs Inc. [Online]. DirectLink OEQuest. (2012, Sep.) OEQuest. [Online]. DirectLink http://www.oclaro.com/datasheets/Oclaro_PowerBit_F10_v1_2.pdf DirectLink